Analisis Tindak Tutur Direktif Pada Interaksi Guru dan Siswa Kelas VII SMP Negeri 13 Kota Bengkulu - Ibrahim, Nanjul; Risnawati, Risnawati; Astuti, Dian Putri Juni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This research aims to analyze directive speech acts in interactions between teachers and students in class VII of SMP Negeri 13 Bengkulu City. The research method used is descriptive qualitative with observation techniques and documentation studies. The research results show that the dominant directive speech acts are commands, requests, invitations and advice. Teachers use command speech acts to give firm instructions, while request speech acts are used to ask for something politely. Apart from that, the speech act of invitation is used to invite students to do something voluntarily, and the speech act of advice is used to give suggestions or instructions to students. In conclusion, teacher and student interactions in class VII of SMP Negeri 13 Bengkulu City are dominated by various directive speech acts, showing the dynamics of effective communication in the learning process. Keywords: Analysis, Teacher-Student Interaction, Directive Speech Act